An Innovative Design of Strip and Circular Footings on Sand Surface: Stress–Density Framework - Ramadan, Mohamed I. (Civil Engineering Journal, 2025)
The bearing capacity of shallow foundations subjected to vertical centric loads has been extensively investigated. Despite the variability in the bearing capacity factor Nγ as proposed by different methodologies, the classical solution remains dominant in design codes. Critical variables affecting the bearing capacity of sand encompass sand particle morphology, footing width or diameter (B or D), mean effective stress level (p'), and sand relative density (Dr). Different sand types may exhibit distinct mobilization friction angles (ϕm) at the same Dr and p', resulting in varied stress-strain behaviors. Thus, the actual bearing capacity may not be accurately reflected by estimates of Ngamma derived from a constant peak friction angle (ϕp) value. In this study, a Three-Dimensional Finite Element Model (3D-FEM) has been applied to both strip and circular footings, employing a hypoplastic constitutive sand model to replicate sand behavior. The model efficiently replicates the compression and shear behavior of sand across a wide range of confining pressures and densities. A comprehensive parametric analysis has been conducted, encompassing a broad range of parameter variations. The principal objective is to present an innovative design approach concerning the bearing capacity of footings for diverse sand characteristics across an extensive array of sand properties. Additionally, a correlation has been established between the bearing capacity factors for strip and circular footings.   Doi: 10.28991/CEJ-2025-011-03-03 Full Text: PDF